Simulation Study of an Arduino-Driven Heart Monitoring System for Maternal Well-Being - Nazif, D. M.; Umar, Sadiq; Ahmad, Muhammad Aminu; Abdullahi, Nasiru; Nghalmi, S. B.; Abdulrahman, Aliyu (Mikailalsys Journal of Advanced Engineering International, 2025)
Maternal cardiovascular health significantly influences pregnancy outcomes; however, conventional monitoring practices often depend on sporadic clinical evaluations, hindering the prompt identification of potential abnormalities. This study presents the design and simulation of a cost-effective, Arduino-based maternal heart monitoring system intended to facilitate early detection of cardiovascular irregularities during pregnancy. The system was developed using Proteus 8.15 simulation software and comprises an Arduino Uno microcontroller, a virtual heartbeat sensor, an LCD display, LED indicators, and buzzer alarms. The simulated environment replicates real-time physiological signal acquisition, processing, classification, and alert generation across various heart rate scenarios, including bradycardia, tachycardia, and normal rhythms. The system accurately classified these conditions and triggered appropriate audiovisual alerts during abnormal episodes. Signal fidelity was verified using a virtual oscilloscope, and the system reliably identified critical thresholds such as severe bradycardia (≤25 BPM) and tachycardia (≥145 BPM). These results underscore the potential of the proposed solution as an offline, low-cost monitoring tool particularly suitable for deployment in resource-constrained settings. Future research should advance this work through physical prototyping, integration with fetal monitoring systems, and empirical validation in clinical and rural contexts to assess its practical efficacy and scalability.